(untitled) (Swiss Medical Weekly, 2010)
QUESTIONS UNDER STUDY: To date, there are hardly any studies on the choice of career path in medical school graduates. The present study aimed to investigate what career paths can be identified in the course of postgraduate training of physicians; what factors have an influence on the choice of a career path; and in what way the career paths are correlated with career-related factors as well as with work-life balance aspirations. METHODS: The data reported originates from five questionnaire surveys of the prospective SwissMedCareer Study, beginning in 2001 (T1, last year of medical school). The study sample consisted of 358 physicians (197 females, 55%; 161 males, 45%) participating at each assessment from T2 (2003, first year of residency) to T5 (2009, seventh year of residency), answering the question: What career do you aspire to have? Furthermore, personal characteristics, chosen specialty, career motivation, mentoring experience, work-life balance as well as workload, career success and career satisfaction were assessed. Career paths were analysed with cluster analysis, and differences between clusters analysed with multivariate methods. RESULTS: The cluster analysis revealed four career clusters which discriminated distinctly between each other: (1) career in practice, (2) hospital career, (3) academic career, and (4) changing career goal. From T3 (third year of residency) to T5, respondents in Cluster 1–3 were rather stable in terms of their career path aspirations, while those assigned to Cluster 4 showed a high fluctuation in their career plans. Physicians in Cluster 1 showed high values in extraprofessional concerns and often consider part-time work. Cluster 2 and 3 were characterised by high instrumentality, intrinsic and extrinsic career motivation, career orientation and high career success. No cluster differences were seen in career satisfaction. In Cluster 1 and 4, females were overrepresented. CONCLUSION: Trainees should be supported to stay on the career path that best suits his/her personal and professional profile. Attention should be paid to the subgroup of physicians in Cluster 4 switching from one to another career goal in the course of their postgraduate training.